Effect of fat source on performance of weaned pigs - Turlington, W.H.; Allee, G.L.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 5-week trial was conducted to compare various fat sources for the weaned pig. A total of 150 pigs were weaned at 19 days of age and allotted, by weight, to five dietary treatments. Treatments consisted of a control with no added fat and four fat sources (choice white grease, coconut oil, soybean oil and tallow). During the first 2 weeks, 10% fat was added, and 5% fat was added during the last 3 weeks. Average daily gain and feed/gain of weaned pigs were improved with the addition of dietary fat. During the first 2 weeks, pigs fed soybean oil had superior performance to other pigs fed additional fat. During the last 3 weeks and over the entire 5 week study pigs fed choice, white grease and soybean oil had a faster rate of gain and were more feed efficient than pigs fed the other fat sources. Among the four fat sources, tallow appeared to be least effective at improving pig performance.
Keywords: Swine